Exploring The Relationship Between Physical Activity and Mental Health in College Students - Omar Kadhim; Layla Rashid (International Journal of Health and Social Behavior, 2024)
This study explores how physical activity impacts mental health outcomes in college students. By examining data on exercise frequency, stress levels, and academic performance, the research identifies a positive correlation between regular physical activity and improved mental health, including reductions in stress and anxiety. The findings suggest that promoting physical activity could enhance mental well-being among students and improve academic performance.